The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/polym13050687
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Biotechnological Potential of Intracellular Polyhydroxybutyrate by Stigeoclonium sp. B23 Using Cassava Peel as Carbon Source

Abstract: The possibility of utilizing lignocellulosic agro-industrial waste products such as cassava peel hydrolysate (CPH) as carbon sources for polyhydroxybutyrate (PHB) biosynthesis and characterization by Amazonian microalga Stigeoclonium sp. B23. was investigated. Cassava peel was hydrolyzed to reducing sugars to obtain increased glucose content with 2.56 ± 0.07 mmol/L. Prior to obtaining PHB, Stigeoclonium sp. B23 was grown in BG-11 for characterization and Z8 media for evaluation of PHB nanoparticles’ cytotoxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 76 publications
(118 reference statements)
0
3
0
Order By: Relevance
“…In order to address these challenges, several studies have put forth various alternatives aimed at mitigating manufacturing expenses [39]. These alternatives include utilizing industrial residues as substrates for raw materials [40], chemically modifying PHA, employing genetic engineering techniques to enhance cell growth, manipulating cell morphology, and enhancing characteristics such as altering synthesis pathways [41].…”
Section: Pha In Biotechnologymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to address these challenges, several studies have put forth various alternatives aimed at mitigating manufacturing expenses [39]. These alternatives include utilizing industrial residues as substrates for raw materials [40], chemically modifying PHA, employing genetic engineering techniques to enhance cell growth, manipulating cell morphology, and enhancing characteristics such as altering synthesis pathways [41].…”
Section: Pha In Biotechnologymentioning
confidence: 99%
“…Impallomeni et al [62] and Mohandas et al [49] showed promising results for the development of carriers from MCL-PHA produced by Pseudomonas aeruginosa ATCC 27853 and PHA copolymer produced by Bacillus cereus MCCB 281 using glycerol as a carbon source, respectively. Mourão et al [40] showed the potential for adaptive PHB production for drug carriers by the Amazonian microalgae Stigeoclonium sp. B23 using hydrolyzed cassava bark as substrate.…”
Section: Drug Carriersmentioning
confidence: 99%
“…The majority of published articles (73%) are studies performed on a single species of algae, followed by experiments conducted on two species (12.16%). Interestingly, one study focused on the production of NPs (specifically silver and AgNPs) using seven different species of algae (Chlorophyta, Charophyta, and Cyanobacteria) [39]. In detail, 68 other species of algae belonging to 45 families are reported in the documents corpus.…”
Section: Relevant Species and The Importance Of Species Characterizationmentioning
confidence: 99%